CORAZ MNIEJ GRZESZNI - O KATEGORII GRZECHU W ŚWIADOMOŚCI MŁODYCH LUDZI - Królikowska, Anna (Wydział Prawa i Administracji UAM, 2006)
Among European nations Poles are recognised as highly religious. Current declarations of religious faith do not mean, however, that people’s religiousness meets the expectations and teaching of Catholic Church. Sin is a notion relatively strongly fixed within the Christian and Catholic doctrine. Contemporary culture is conducive to the decrease of the influence of this notion on consciousness and religious and moral life. Sin as a notion is almost absent in a social sphere outside the Church. Can it be found within an individual consciousness? This question, like those on the condition of other religious notions, is interesting particularly in reference to young people, whose consciousness is, on the one hand, under the influence of postmodern cultural values, and on the other, has been equipped with some traditional, religious transmission. If a category of sin still remains, then what are its versions and interpretations? What are its equivalents in a secularised consciousness? Theoretical and methodological questions referring to the changes in interpretations of the notions that played important roles in our culture are still a separate issue. The argument that an exploration o f such a private sphere goes beyond the limits of sociology is not strong enough to induce withdrawal of our interest from that part of human consciousness.
INCREASINGLY LESS SINFUL - ON THE SIN IN YOUNG PEOPLES’ CONSCIOUSNESS